Share of voices in corporate social responsibility (CSR) news: A comparison of sources used in press releases and news coverage. (13th February 2019) - Tam, Lisa
Abstract : Purpose: The use of sources in news coverage affects news audience's perceptions of news events. To extend existing research on inter media agenda-setting and agenda-building effects of CSR-related news, the purpose of this paper is to explore the representation and share of voices in CSR-related news by investigating and comparing the use of sources in press releases and news coverage. Design/methodology/approach: This study content-analyzed the 202 CSR-related press releases published by the two electricity providers in Hong Kong and 1, 045 news articles related to the press releases over a five-year period. A total of 402 quotes from the press releases and 1, 880 quotes from the news coverage were analyzed, including the types of sources cited, the tone of the sources and variations in the use of sources across seven different CSR themes. Findings: Although company representatives were quoted the most in both the press releases and news coverage, NGOs, government representatives and industry analysts were the most frequently cited for negative comments in the news coverage. Differences were found between the press releases and news coverage in terms of how frequently different sources were cited, the tone attributed to those sources, and the choice of sources across different CSR themes. Originality/value: The findings reflect that corporations are not necessarily the most influential voice in CSR and that other groups also have their views represented in the news media. The representation of these voices differed by CSR themes. Corporations are advised to further explore what and how different voices are represented in the news coverage in relation to their CSR activities and to consider these voices when making decisions about CSR.